Mechanical forces instruct division plane orientation of cambium stem cells during radial growth in Arabidopsis thaliana - Höfler, Mathias; Liu, Xiaomin; Greb, Thomas; Alim, Karen (Current biology, 2024)
Robust regulation of cell division is central to the formation of complex multi-cellular organisms and is a hallmark of stem cell activity. In plants, due to the absence of cell migration, the correct placement of newly produced cell walls during cell division is of eminent importance for generating functional tissues and organs. In particular, during the radial growth of plant shoots and roots, precise regulation and organization of cell divisions in the cambium are essential to produce adjacent xylem and phloem tissues in a strictly bidirectional manner. Although several intercellular signaling cascades have been identified to instruct tissue organization during radial growth, the role of mechanical forces in guiding cambium stem cell activity has been frequently proposed but, so far, not been functionally investigated on the cellular level. Here, we coupled anatomical analyses with a cell-based vertex model to analyze the role of mechanical stress in radial plant growth at the cell and tissue scale. Simulations based on segmented cellular outlines of radially growing Arabidopsis hypocotyls revealed a distinct stress pattern with circumferential stresses in cambium stem cells, which coincided with the orientation of cortical microtubules. Integrating stress patterns as a cue instructing cell division orientation was sufficient for the emergence of typical cambium-derived cell files and agreed with experimental results for stress-related tissue organization in confining mechanical environments. Our work thus underlines the significance of mechanical forces in tissue organization through self-emerging stress patterns during the growth of plant organs.
Online verfügbar: 20. November 2024, Artikelversion: 2. Dezember 2024
Gesehen am 05.03.2025